Investigating the dosimetric benefits of modulated electron radiation therapy (MERT) for partial scalp patients. (18th May 2017) - Eldib, Ahmed; Jin, Lihui; Martin, Jeffrey; Fan, James; Li, Jinsheng; Chibani, Omar; Veltchev, Iavor; Price, Robert; Galloway, Thomas; Ma, C-M Charlie
Abstract: Purpose . Modulated electron radiation therapy (MERT) can offer advantages over conventional radiotherapy for the treatment of superficial targets. MERT can effectively achieve conformal dose distributions to shallow tumors while sparing distal critical structures. The aim of the present study is to investigate the potential dosimetric advantage of scalp radiation therapy using MERT as compared with the conventional electron and advanced photon techniques. Methods . Treatment planning was performed for multiple electron beams using an in-house developed Monte Carlo-based inverse planning system, MCPLAN. Treatment optimization was performed based on an equivalent uniform dose objective function and a gradient search algorithm. Treatment planning was based on delivery using a prototype multileaf collimator that has been investigated for MERT. Results . Five previous scalp patients who were treated with volumetric modulated arc therapy (VMAT) were re-planned using MERT treatment technique. PTV coverage was comparable between MERT and VMAT plans. MERT produced a larger hot spot inside the PTV compared to VMAT. The VMAT plan showed larger volumes enclosed by the 50% and 30% isodose surfaces compared to MERT. The mean brain dose was significantly reduced with MERT (422 cGy) compared to that with VMAT (1032 cGy). Both MERT and VMAT treatment plans met our clinical acceptance criteria for skin dose. Conclusions . MERT was able to adequately cover the planned target volume and decrease the dose to the brain when compared to the VMAT plans. MERT was more efficient in treating some of the scalp cases. MERT was shown to be a promising modality for treating scalp cases and could be beneficial to other superficial tumors with complex shapes.